217k views
2 votes
F(x) = -3x + 7 ; reflection in the x-axis

User Brick Yang
by
4.4k points

1 Answer

2 votes

We have that the rule for reflecting over the X axis is to negate the value of the y-coordinate of each point, but leave the x-value the same. In this case we have

With the blue one the relfection of our fuction f, this is because for the rule we have that x = t and y = - (- 3t + 7) = 3t - 7. So the reflection is g(x) = 3x - 7

F(x) = -3x + 7 ; reflection in the x-axis-example-1
User SarahTheButterFly
by
5.3k points